Enhancing swiftlet farmhouse environmental monitoring through IOT technology: A case study in Menumbok, Sabah - Fakhirul aziff hamdan; Marni Azira Markom; Muhammad aizat zaim zaini; Ahmad muzammil roslizar; Hazlihan Haris; Yusrina Yusof; Roslina mohamad; Mohd shahdan harris; Arni Munira Markom (Engineering, 2025)
This research focuses on the development and validation of an Internet of Things (IoT)-based system specifically tailored for environmental monitoring at the HN Swiftlet Farmhouse in Menumbok Sabah. The lack of effective monitoring systems in swiftlet farmhouses presents challenges in maintaining optimal conditions for swiftlet health and productivity. To address this, the study implements IoT technology for real-time data collection and analysis, aiming to sustain optimal breeding conditions. The system integrates a NodeMCU ESP 32 board with a DHT11 sensor to monitor temperature and humidity, providing timely notifications and facilitating automated control procedures. Over a nineday observation period, temperatures ranged from 31.23 °C to 33.33 °C, and humidity levels ranged from 59.63% to 77.38%, with fluctuations influenced by monsoon activity. The findings indicate that the IoT-based system effectively assists swiftlet farmers in maintaining optimal environmental conditions, thereby enhancing swiftlet health and productivity. The research demonstrates that the implementation of IoT technology in swiftlet farmhouses significantly enhances environmental monitoring, leading to improved swiftlet health, increased productivity, and overall sustainability in swiftlet farming practices.